2014
DOI: 10.1161/str.0000000000000016
|View full text |Cite|
|
Sign up to set email alerts
|

Cervical Arterial Dissections and Association With Cervical Manipulative Therapy

Abstract: 3155Purpose-Cervical artery dissections (CDs) are among the most common causes of stroke in young and middle-aged adults.The aim of this scientific statement is to review the current state of evidence on the diagnosis and management of CDs and their statistical association with cervical manipulative therapy (CMT). In some forms of CMT, a high or low amplitude thrust is applied to the cervical spine by a healthcare professional. Methods-Members of the writing group were appointed by the American Heart Associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(108 citation statements)
references
References 233 publications
(348 reference statements)
3
78
0
11
Order By: Relevance
“…Cervical artery dissection is a rare event and case-control studies have consistently found an association with cervical spine manipulation (Biller 2014; Church 2016). However, the best evidence suggests that the association is not causal.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical artery dissection is a rare event and case-control studies have consistently found an association with cervical spine manipulation (Biller 2014; Church 2016). However, the best evidence suggests that the association is not causal.…”
Section: Introductionmentioning
confidence: 99%
“…Trauma to the internal carotid artery likely occurs due to cervical extension or sudden neck movement compressing the artery over the bodies or transverse processes of the upper cervical vertebrae or mastoid process . The vertebral artery is most commonly injured at the atlanto-axial segment (C1-2) where most cervical rotation occurs (Biller et al 2014, Bogduk and Mercer, 2000, Haneline and Triano, 2005, Lleva et al 2012. (Figure 3)…”
Section: Aetiologymentioning
confidence: 99%
“…The questions raised are whether the nature of a manipulative technique is responsible for the dissection, or whether the diagnosis of CAD has been missed (Biller et al, 2014).…”
Section: Cad and Manipulative Therapy Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Trauma is a frequent cause of cervical dissection, making a thorough history important in establishing the correct diagnosis. Although an association between cervical dissection and cervical manipulative therapy (chiropractor manipulation) has been established, on the basis of clinical reports and population-control studies, the 2014 American Heart Association/American Stroke Association scientific statement concluded there is insufficient evidence to establish the claim that mechanical forces generated during such manipulative therapy are the cause of the dissection [44].…”
Section: Headaches Due To Cervical Artery Dissectionmentioning
confidence: 99%